Safety and tolerability of moxifloxacin in the treatment of respiratory tract infections: a post-marketing surveillance conducted in Indonesia (Faculty of Medicine Universitas Indonesia, 2005)
Moxifloxacin 400 mg tablet has been marketed in Indonesia for several indications, i.e. acute exacerbation of chronic bronchitis (AECB), community-acquired pneumonia (CAP), and acute bacterial sinusitis (ABS). To assess the safety and tolerability of moxifloxacin, a post-marketing surveillance study was conducted in the year 2001 involving 589 physicians. Clinical efficacy was also evaluated, both by physicians and patients, using a 6-symptom total score, which was scaled 0-12. A total of 1715 patients with acute sinusitis, CAP, AECB, and other infections were treated with oral moxifloxacin 400 mg once daily. There were 151 (8.8%) patients with adverse events (AEs) and 5 (0.29%) patients with serious adverse events (SAEs) that were considered related to moxifloxacin treatment. The most common adverse reactions were nausea (4.96%), dizziness (1.52 %), vomiting (0.64%), headache (0.47%), andweakness (0.47%). Twenty three (1.34%) patients discontinued treatment due to adverse events. Tolerance to treatment was rated very good and good by 647 (37.7%) and 919 (53.6%) of patients, respectively. Based on physicians’ clinical assessment, 57.7% of patients were cured and 39.9% were improved at the end of treatment. Mean total symptom score, as assessed by the patients, decreased from 6.43 on day-1 to 2.76 on day-3. Totally, 95.3% of patients felt better after receiving moxifloxacin and 97.6% of patients had good impression on moxifloxacin treatment. In conclusion, treatment of respiratory tract infections, mainly AECB, CAP and ABS, with moxifloxacin 400 mg once daily in this post-marketing surveillance was shown to be safe and well tolerated. Moxifloxacin was also shown to be highly effective in the treatment of these infections with rapid improvement of symptoms. (Med J Indones 2005; 14: 11-19) Keywords : post-marketing survtillance, PMS, moxifloxacin, respiratory tract infections